Phylogenetic tests reject Emery's rule in the evolution of social parasitism in yellowjackets and hornets (Hymenoptera: Vespidae, Vespinae) - Lopez-Osorio, Federico (R Soc Open Sci, 2015)
Social parasites exploit the brood-care behaviour and social structure of one or more host species. Within the social Hymenoptera there are different types of social parasitism. In its extreme form, species of obligate social parasites, or inquilines, do not have the worker caste and depend entirely on the workers of a host species to raise their reproductive offspring. The strict form of Emery's rule states that social parasites share immediate common ancestry with their hosts. Moreover, this rule has been linked with a sympatric origin of inquilines from their hosts. Here, we conduct phylogenetic analyses of yellowjackets and hornets based on 12 gene fragments and evaluate competing evolutionary scenarios to test Emery's rule. We find that inquilines, as well as facultative social parasites, are not the closest relatives of their hosts. Therefore, Emery's rule in its strict sense is rejected, suggesting that social parasites have not evolved sympatrically from their hosts in yellowjackets and hornets. However, the relaxed version of the rule is supported, as inquilines and their hosts belong to the same Dolichovespula clade. Furthermore, inquilinism has evolved only once in Dolichovespula.